Given:
To get rid of the fraction, we can multiply both sides by the denominator, which is 3. This will cancel the fraction:
We are left with:
Steps to solving equations:
Simplify/combine the like terms
Isolate the variable (Get the variable on one side
Solve for the variable
-2y - 7 + 5y = 13 - 2y Simplify/Combine terms
3y -7 = 13 - 2y Isolate variable by adding 2y to both sides
5y - 7 = 13 Add 7 to both sides to get y alone on one side
5y = 20 Divide by 5 on both sides to solve for y
y = 4
You can check your answer by replacing y with 4 in the original equation.
Answer:
x =3
Step-by-step explanation:
3(4x + 4) = 2(5x+9) - 12
First step is to open the brackets by multiplying. It becomes
3×4x + 3×4 = 2×5x + 2×9 -12
12x + 12 = 10x + 18 - 12
Collecting like terms on the right hand side and left hand side of the equation, it becomes
12x -10x = 18 -12 -12
2x = -6
Negative sign on the right hand side of the equation overwhelms the positive sign on left hand side of the equation. It becomes
2x = -6
x = -6/2 = -3
Checking
3(4×-3 + 4) = 2(5×-3+9) - 12
-24 = -12-12= -24
So x = -3
Answer:
B
Step-by-step explanation: